Examining the relationship between perceived social support and prenatal distress in pregnant women - Sabet, Somayae Abdollahi; Ahmadi, Samira; Pakian, Zahra; Maleki, Azam (Frontiers in Psychiatry, 2025)
BackgroundUnderstanding the link between perceived social support and prenatal distress is vital for improving maternal mental health during pregnancy.ObjectiveTo examine the relationship between perceived social support and prenatal distress among pregnant women.MethodsA cross-sectional study was conducted on 220 pregnant women at Ayatollah Mousavi Hospital in Zanjan City in 2023. Participants were selected through a convenience sampling method, and data were collected using the Prenatal Distress and social support questionnaires. The analysis involved Spearman’s rank correlation, the Mann–Whitney U test, the Kruskal–Wallis test, and backward conditional logistic regression with median cut-off points, all at a 95% confidence level.ResultsThe average perinatal distress score was 39.38 (SD = 6.04), and the average social support score was 45.66 (SD = 10.91). Total social support was negatively correlated with overall prenatal distress (r = -0.355), childbirth and the baby-related distress (r =-0.472), and emotional/relational issues(r = -0.119), but not with body image-related distress (r = 0.090, p = 0.35). Younger, higher-educated women with more children reported lower distress. Additionally, women aged 18-25, with more children, low income, who were housewives, or had a gestational age of 29–42 weeks, had higher social support scores (p < 0.01).ConclusionBoth perinatal distress and perceived social support were observed at moderate levels among the study population. Parity emerged as the only independent predictor for both prenatal distress and social support, with primiparous women exhibiting higher distress levels, while multiparous women reported higher perceived social support. These findings underscore the importance of developing tailored interventions that address the distinct needs of women according to their parity status.